Strategic Management of Continous Professional Development of Madrasa Supervisors Ministry of Religion Republic of Indonesia - Barnawi Barnawi; Ulfiah Ulfiah; Ikka Kartika A Fauzi; Deti Rostini (STAI Hubbulwathan Duri, 2023)
The results of the supervisory competency assessment on average from each province in the aspect of ealuation and supervision of education are in the proficient category so it is important to make efforts to improve through Continuous Professional Development. The purpose of this study is to describe and analyze the strategic management of Sustainable Professional Development for Madrasah supervisors at the Ministry of Religion of Cirebon. Continuing Professional Development is an effort to deepen knowledge as a madrasa supervisor, so that the substance of CPD is to seek knowledge as well as a form of reconstruction of new knowledge within the supervisor. The method used in this research is qualitative research with descriptive research type. The results of the study indicate that the strategic mangement of the Sustainable Professional Development of Madrasah supervisors has been running effectively and efficiently. The synergy between stakeholders, both the government, the organizing committee, and the participants, has been well realized so that the implementation the CPD for madrasah supervisors is in accordance with the formulation of the established strategy. The implication of this research is that all stakeholders work together to implement CPD in a sustainable manner to increase the capacity of madrasah supervisors